Optimalisasi Tanaman Serai sebagai Bahan Alami Anti Nyamuk untuk Pencegahan Demam Berdarah Dengue - Kusnadi; Hariansyah, Rizal; Maulana, Chelvin; Alianty, Andara; Negara, Eka Estiningsih Dwi; Arrasyid, Qamarudin; Rahmawati, Aulia Tri (Forum Kerjasama Pendidikan Tinggi, 2025)
Dengue Hemorrhagic Fever (DHF) remains a major health concern in Indonesia, including Tanjung Harapan Village, and Kutai Kartanegara. This community service program aimed to develop a strategy utilizing lemongrass (Cymbopogon citratus) as an effective mosquito repellent for DHF prevention in Tanjung Harapan. Employing an environmentally friendly approach, the program involved community education and training on processing lemongrass into mosquito repellent sprays and mosquito control methods. Results indicated increased community knowledge about DHF risks and the benefits of lemongrass. Mosquito nest eradication and lemongrass planting reduced mosquito populations and improved public health. With local resource utilization, this effort offers a sustainable solution to decrease DHF cases and empower the local economy. The activities effectively improved participant knowledge, awareness, and motivation by 71.2%, demonstrating the program's success in achieving its educational and community empowerment goals.